Influence of Non-uniform Wear on Modal Characteristics of Spur Gears - Kaiwen Lu; Juan Zhao; Jie Sun; Menghua Tan; Songnian Liu (Jixie chuandong)
The influence of non-uniform wear on the modal characteristics of gears under quasi-static condition is studied. Based on Hertz contact theory and Archard formula， a quasi-static wear model is established to simulate the wear of gear tooth surfaces. The calculation results show that the wear at the top and root of the driving and driven gears is larger， the wear at the top is smaller than that at the root， the wear at the root of the driving gears is the largest. The pure rolling of the gear at the node does not cause wear， and the wear at the alternation of single tooth and double tooth meshing zones has a mutation. Based on the numerical analysis results， the tooth surface wear fault is applied and imported into Abaqus for simulation， and the modal characteristics of the gear before and after wear are further analyzed. The simulation results show that the gear has a variety of vibration modes， the effect of wear on the vibration modes is not obvious， the natural frequency increases significantly， the increase amplitude of the high natural frequency of the seventh order to the tenth order is higher than that of the low order natural frequency.